2015
DOI: 10.1101/014795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term field experiment on the impacts of the neonicotinoid dinotefuran and the organophosphate fenitrothion on a honeybee colony

Abstract: Summary Neonicotinoides are persistent and highly toxic pesticides that have become popular instead of organophosphates, being suspected to be a trigger of massive disappearance of bees that raises concern in the world. The evaluation of the long-term influence for a whole colony in the natural environment is, however, not established yet. In this paper, we conducted a long-term field experiment and found different impacts on honeybee colonies (Apis mellifera) in an apiary between the neonicotinoid dinotefuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Perhaps, that is the reason why the observed alterations were not statistically significant. Possibly, larvae might have used energy for detoxification from another source, such as trehalose from hemolymph [ 37 , 38 ], which level was not examined in our studies. In the case of the second variant of our experiment, each used concentration decreased glycogen level significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, that is the reason why the observed alterations were not statistically significant. Possibly, larvae might have used energy for detoxification from another source, such as trehalose from hemolymph [ 37 , 38 ], which level was not examined in our studies. In the case of the second variant of our experiment, each used concentration decreased glycogen level significantly.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, to select suitable reference genes, we chose five candidate reference genes including 40S ribosomal protein S5 (RPS5), 40S ribosomal protein S18 (RPS18), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), ADP-ribosylation factor 1 (ARF1), and Rasrelated protein Rab-1A (RAD1a), which have been previously used as reference genes in honey bee studies [28,30,32]. Previous studies showed that honey bee is accidently exposed to various pesticides, and exposure of these pesticides negatively affect honey bee colonies, therefore, we chose seven pesticides (neonicotinoids: acetamiprid and imidacloprid, butanolide: flupyradifurone, organophosphate: fenitrothion, carbamate: carbaryl, formamidine: amitraz, and pyrethroid: bifenthrin) [33][34][35][36][37][38]. In addition, considering that different tissues might involve different detoxification mechanisms [39], we dissected five body parts (head, thorax, gut, fat body, and carcass) from honey bees treated with the seven pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…At position 4, a halogen was clearly preferred (cfr. 5-fold higher activity of 2 compared to 1), since the analogues carrying a methyl (17) or nitro group (19) were less active, while trifluoromethyl 8 (18) was detrimental. In line with the positive effect of the 4-F atom, even slightly higher potency was seen with the 4-chloro analogue 20.…”
Section: Analysis Of Anti-influenza Virus Activitymentioning
confidence: 99%
“…The choice of a piperidine heterocycle was motivated by its pivotal role in drug design [17]. Recently reported pharmacological uses of diverse substituted piperidine derivatives include coronary heart disease, anticancer, antivirals, and antinociceptives, among others [18][19][20][21][22]. In fact, one of the most frequently used non-aromatic ring systems in small molecule drugs is the piperidine ring [23], particularly 1,4disubstituted piperidine, due to its easy synthesis and lack of stereochemical issues.…”
mentioning
confidence: 99%